Attenuating risks and difficulties in Welding pipelines and offshore structures using the underwater welding process - A Review - Hussein, Aws Abbas; Farhan, Fadhil Kareem (Journal of engineering sciences and information technology, 2022)
Oil and gas pipelines, marine application, offshore structures are subjected to aggressive environment which causes corrosion and fatigue in some parts of them. Thus, they need to repair as soon as possible. Underwater welding is used for that purpose which is suitable for urgent repairs. Both types of underwater welding (wet and dry) suffer from many Risks and difficulties that affect the life of welder, on the other hand, reduce the mechanical properties of welds. In this article, the challenges associated with the underwater welding process and methods of treating them or minimizing their effects are reviewed.
Keywords: underwater welding; dry underwater welding; wet underwater welding